TEKNIK HYPNOCOUNSELING DAN DZIKIR DALAM MEREDUKSI STRES PADA REMAJA: INTEGRASI PENDEKATAN PSIKOLOGIS DAN SPIRITUAL - Mudiuddin, Mudiuddin; Nur Hidayah; Fitri Wahyuni (UIN Sunan Kalijaga Yogyakarta, 2024)
This study explore the effectiveness of hypnocounseling and dhikr in reducing stress in adolescents. Adolescents are vulnerable to psychosocial pressures, such as academic demands, family conflicts, and social interactions, which can have a negative impact on mental health. Hypnocounseling is known as a technique that utilizes the subconscious mind to reduce anxiety, while dhikr serves as a spiritual relaxation method that calms the mind. However, studies integrating these two approaches are limited. This study used a systematic literature review method by analyzing 19 related articles from 2020-2024. The results showed that the combination of hypnocounseling and dhikr is effective in increasing self-awareness, emotional control, and inner calm, which helps adolescents manage stress better. This approach also has the potential to reduce the negative impacts of prolonged stress, such as excessive anxiety and destructive behavior. This study contributes to the development of psychology and spiritual-based guidance and counseling, especially in the context of Islamic education and pesantren. With a holistic approach, the integration of hypnocounseling and dhikr can be an effective strategy in supporting adolescent mental health Keywords: Hypnocounseling, Dhikr, Adolescent Stress, Spiritual Counseling